2019
DOI: 10.32463/rphs.2019.v05i03.02
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Ocimum americanum In Sudan

Abstract: Plants are one of the most important of medicines. Basil (Ocimum americanum) is one such plant which symbolize all that is extraordinary in nature because the entire whole plant has been used traditional medicine for household remedy against various human from antiquity. The genus O.americanum is known to include species accumulating essential oils. In this study the secondary metabolites of both flowers and leaves of O.americanum which occur in the central Sudan. The proximate analysis to samples showed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The ash content is a reflection of its mineral content. The ash content of the leaves compared to the flowers presents that the minerals are more concentrated in the leaves than in the flowers (Mustafa and El-kamali, 2019).…”
Section: Proximate Compositionmentioning
confidence: 98%
See 2 more Smart Citations
“…The ash content is a reflection of its mineral content. The ash content of the leaves compared to the flowers presents that the minerals are more concentrated in the leaves than in the flowers (Mustafa and El-kamali, 2019).…”
Section: Proximate Compositionmentioning
confidence: 98%
“…It is also been reported to have antifungal properties Tannins are khoum to exhibit antiviral, antibacterial and anti-tumor activities. It was also reported that certain tannins are able to inhibit HIV replication (Mustafa and El-kamali, 2019).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…From table 1. The Saponin found in all plants except in Hydnora abysinica, Saponins are steroidal glycosides with foaming characteristics and bitter taste that have beneficial effect on the blood cholesterol levels, fight cancer and help in health and the stimulation of immune system [15] . Saponins have hemolytic properties and are used as starting materials for the synthesis of steroidal drugs like corticosteroids, the sex hormone stimulants and contraceptives [16] .…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Many phytochemicals found in plants are either the product of plant metabolism or synthesized for defence purposes. The phytochemicals are either useful or toxic to human body [15] . Key: + = present; _ = Absent…”
Section: Phytochemical Screeningmentioning
confidence: 99%